Towards Benchmarking User Stories Estimation with COSMIC Function Points-A Case Example of Participant Observatio - Jayasri Angara; Srinivas Prasad; Gutta Sridevi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Shorter time-to-market and unstable requirements is leading to introduction of Agile and DevOps practices. Story point estimation is becoming handier in Agile/DevOps setting. However, developing user stories and defining sizing unit in terms of story point is subjective process. It lacks benchmarking/standardization in terms of sizing measure and productivity of historical data. COSMIC has been considered as FSM (Functional Size Method). It has flexibility to receive requirements as User stories (popular Agile/Devops method) and derive COSMIC functional units using parametric approach. COSMIC method reduces the subjectivity and populates the productivity parameter for benchmarking. It standardizes the estimation process and can be easily deployed in Agile or DevOps setting. This paper presents the related work on linkages between User stories, COSMIC methods and traditional function point methods. It also presents the outcome of the industry survey conducted on 49 practitioners working in 10 different domains with respective to parametric estimation process adoption and presents 9 real-time case studies developed to demonstrate the usage of COSMIC method in various domains. This paper also attempts to derive mapping process of COSMIC functional process with User Stories with the help of 2 real-time industry case studies.